2018
DOI: 10.3390/ijerph15091907
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation by the Ames Assay of the Mutagenicity of UV Filters Using Benzophenone and Benzophenone-1

Abstract: Ultraviolet absorbing chemicals (UV filters) are widely used in personal care products for protecting human skin and hair from damage by UV radiation. Although these substances are released into the environment during production and consumption processes, little is known about their genotoxicity effects. Our previous studies have shown that benzophenone-type UV filters exhibited acute toxicity on three species of aquatic organisms. Mutagenesis by benzophenone (BP) and benzophenone-1(BP-1) was tested in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…However, in two cases, when S. typhimurium TA1537 was tested in the absence and presence of a metabolic activation system (S9), the MR was found to be ≥ 2 ( Table 6). This could indicate a slight potential for mutagenicity (Pah and Lakhani, 2012;Wang et al, 2018) which was also predicted in silico ( Table 5). In the present study, S9 was derived from rat liver, and notably, previous studies have shown that the outcome of the Ames test may vary according to whether S9 is prepared from rat or human liver extract (Hakura et al, 2005).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, in two cases, when S. typhimurium TA1537 was tested in the absence and presence of a metabolic activation system (S9), the MR was found to be ≥ 2 ( Table 6). This could indicate a slight potential for mutagenicity (Pah and Lakhani, 2012;Wang et al, 2018) which was also predicted in silico ( Table 5). In the present study, S9 was derived from rat liver, and notably, previous studies have shown that the outcome of the Ames test may vary according to whether S9 is prepared from rat or human liver extract (Hakura et al, 2005).…”
Section: Discussionsupporting
confidence: 65%
“…The Ames test was performed as described in Supplementary Material where acceptance criteria for the test results can also be found. To evaluate the test results, the mutagenicity ratio (MR) was calculated and interpreted as in previous studies ( Pah and Lakhani, 2012 ; Wang et al, 2018 ). The MR was calculated as MR = x / x n .…”
Section: Methodsmentioning
confidence: 99%
“…The pathogenesis is likely related to the failure of neural crest cells to migrate to the distal hindgut during fetal organogenesis, specifically during weeks 5 to 12. Other studies suggest possible correlations with uterine leiomyoma formation and increased mobility of breast and lung cancer cells ( Alamer and Darbre, 2018 , Pollack et al, 2015 , Phiboonchaiyanan et al, 2017 , Wang et al, 2018 ) (see Table 2 ).…”
Section: Human Health Impact Of Uv Filter Exposurementioning
confidence: 95%
“…A compound was labeled Ames positive if it significantly induces the development of the reverting colony in at least one of the five strains. If a compound was positive for the Ames test, it could be a possible mutagen 39 . Ames mutagenicity was conducted in four methods for all of the chosen compounds, and the findings were comparatively analyzed in Table VI.…”
Section: Ames Mutagenicitymentioning
confidence: 99%